JARINGAN SOSIAL ORGANISASI LESBIAN, BISEXUAL, DAN TRANSGENDER: STUDI KASUS ORGANISASI ARDHANARY INSTITUTE DI JAKARTA - Sri Setiawati (Universitas Andalas, 2016)
This paper discusses the social networks that is done by Ardhanary Institute LBT Women (Lesbian, Bisexual, Transgender) organization in Jakarta. With the thesis that the environment in Indonesia are not permissive and cons with the presence of LGBT / LBT this organization even dare to